Municipality-Level Source Apportionment of PM2.5 Concentrations based on the CAPSS 2016: (IX) Gyeongsangbuk-do - Son, Segi Kim Kyuwon; You, Seunghee; Bae, Minah; Kang, Yoon Hee; Kim, Eunhye; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2022)
In this study, we estimated contributions of foreign and domestic emissions to the annual mean PM2.5 concentration in Gyeongbuk for 2016 using Comprehensive Air Quality Model eXtensions with Particulate Source Apportionment Technology. For the detailed analyses on the domestic contributions, self- and inter-provincial contributions as well as intermural contributions among twenty-two local authorities, excluding Ulleung, in the province were estimated based on the CAPSS 2016 emissions inventory (EI). The simulated annual mean PM2.5 concentration in Gyeongbuk was 20.9 pg/m3 for the year. The domestic contributions to the annual mean PM2.5 concentrations over the local authorities ranged from 3.6 to 13.7 pg/m3. Provincial self-contribution to the annual mean PM2.5 concentration in Gyeongbuk was 3.6 pg/m3, explaining 44% of the domestic contribution. It implies that collaboration with neighboring provinces is essential to improve the air quality over Gyeongbuk. The contributions of Chungnam and Gyeonggi to the annual mean PM2.5 concentration in Gyeongbuk were 1.0 pg/ m3 and 0.8 pg/m3. Among 22 local authorities, Pohang showed the highest emission rates of PM2.5-related air pollutants, and thus the highest local authority-level self-contribution. However, the annual mean PM2.5 concentration in Pohang was overpredicted by 61.8 pg/m3. Compared to the EI-based contribution, adjusted PM2.5 self-contribution of Pohang using the ratio between the observed and simulated concentrations was reduced by 55%. Considering the over-prediction, especially over the hot-spot area, the emissions inventory used in air quality simulations for the purpose of air quality management should be more thoroughly evaluated prior to analyzing the source-receptor relationship.
Keywords: PM2.5, Source apportionment, Gyeongsangbuk-do, Foreign and domestic contributions, Emissions inventory